2014
DOI: 10.2478/acph-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected catechins on doxorubicin antiproliferative efficacy and hepatotoxicity in vitro

Abstract: Catechins may influence both desirable and undesirable effects of many drugs. In this study, the in vitro effect of (+)-catechin, (-)-epicatechin, (-)-epigallocatechin, (-)-epicatechin gallate, and (-)-epigallocatechin gallate (EGCG) on the efficacy of anticancer drug doxorubicin (DOX) was studied in HCT-8 cancer cells. Rat hepatocytes were used to study the influence of EGCG on DOX hepatotoxicity. Cell proliferation and viability were studied by 3-[4,5-dimethylthiazol- 2-yl]-2,5-diphenyl tetrazolium bromide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…The effects of AC on rat ileum and proximal colon viability and functionality were thus assessed, and results highlighted the safe profile of AC, indicating a selective activity against cancer tissues. This sparing activity was already reported for EGCG and EGC in many cancer cells lines [49][50][51][52][53], and although the precise mechanism is still debated, the lower intracellular copper content of non-malignant cells might constitute the key difference [54]. Finally, AC is endowed with antibacterial activity against Gram-negative (Escherichia coli, klebsiella pneumoniae, Proteus mirabilis and Pseudomonas aeruginosa) and Gram-positive bacteria (Staphylococcus aureus and Streptococcus pneumonia) [11,55]; at the same time it is ineffective toward Lactobacilli and Bifidobacteria, the most represented intestinal species.…”
Section: Discussionsupporting
confidence: 78%
“…The effects of AC on rat ileum and proximal colon viability and functionality were thus assessed, and results highlighted the safe profile of AC, indicating a selective activity against cancer tissues. This sparing activity was already reported for EGCG and EGC in many cancer cells lines [49][50][51][52][53], and although the precise mechanism is still debated, the lower intracellular copper content of non-malignant cells might constitute the key difference [54]. Finally, AC is endowed with antibacterial activity against Gram-negative (Escherichia coli, klebsiella pneumoniae, Proteus mirabilis and Pseudomonas aeruginosa) and Gram-positive bacteria (Staphylococcus aureus and Streptococcus pneumonia) [11,55]; at the same time it is ineffective toward Lactobacilli and Bifidobacteria, the most represented intestinal species.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies confirm the benefits of these compounds in animal models of hepatotoxicity. Rudolfová and colleagues shown that catechin administration during DOX therapy seems to be safe and beneficial, since EGCG does not reduce DOX anticancer efficacy while augment hepatocytes viability could ameliorate DOX hepatotoxicity [51]. Another study revealed that vitamin E and catechin can reduce the toxic effects of DOX in liver by ameliorating the action of key enzymes contributing in free radical metabolism, i.e., superoxide dismutase, glutathione peroxidase (GSHPx), catalase (CAT) and malondialdehyde (MDA) in the hepatic tissues of DOX-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent oxidative damage from anticancer drug tegafur, EGCG was applied to exert its antioxidative effect to restore the expression level of α‐defensin resulting in an immunoprotective effect in human intestinal epithelial cells . Additionally, doxorubicin‐induced cardiotoxicity and hepatotoxicity were attenuated by EGCG via decreased production of ROS and increased protein expression of endogenous antioxidant enzymes and ErbB2 …”
Section: Combinational Effects Of Egcg and Other Anticancer Agentsmentioning
confidence: 99%